用于操作喷射阀的方法 (2019)
本发明涉及一种用于操作喷射阀的方法，该喷射阀的喷嘴针阀通过压电致动器被致动，其中，该喷嘴针阀的动态提升轮廓被确定并被控制。包括致动器电流或致动器负载和/或致动器电压的变量在喷射过程期间被连续检测并且该喷嘴针阀的动态提升轮廓借助于针对喷射阀的喷嘴针阀运动的模型结构被重建，由此导出致动器电流、或致动器负载、和/或致动器电压的目标变量。所述目标变量与实际值相对比，并且所述两个值之间的偏差被最小化。 The present disclosure relates to methods for operating an injection valve. An example method may include capturing ACTUAL quantities constituted by actuator current or actuator charge and/or actuator voltage continuously during an injection process; reconstructing a dynamic progression of the nozzle-needle stroke of an injection valve on the basis of a model structure for a motion of the nozzle needle of the injection valve, ascertaining the DESIRED quantities constituted by actuator current or actuator charge and/or actuator voltage therefrom, wherein the dynamic progression of the nozzle-needle stroke is reconstructed via a simplified model structure by introduction of at least one discrete measured value pertaining to the injection valve into a basic model of the nozzle-needle motion; comparing the DESIRED quan